2019
DOI: 10.3892/ol.2019.10981
|View full text |Cite
|
Sign up to set email alerts
|

Role of apoptosis repressor with caspase recruitment domain (arc) in cancer (Review)

Abstract: Apoptosis repressor with caspase recruitment domain (ARC) is a potent inhibitor of apoptosis. Under physiological conditions, ARC is abundantly expressed in terminally differentiated cells, including cardiomyocytes, skeletal muscles and neurons. ARC serves a key role in determining cell fate, and abnormal ARC expression has been demonstrated to be associated with abnormal cell growth. Previous studies have revealed that ARC was upregulated in several different types of solid tumor, where it suppressed tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…We determined by qRT-PCR that S. cuneifolia extracts showed apoptosis-triggering effects on pro-apoptotic and anti-apoptotic gene expressions in DLD1 cells. In the present study, apaf-1, tp53, card4 and Casp-3 genes were found to be upregulated in cancer cells after exposure to these extracts; these proteins play an important role in tumour suppression, cell cycle arrest and application phase of cell apoptosis (Delbridge et al, 2012;Kao et al, 2015;Kobayashi et al, 2000;Mattson and Bazan, 2012;Umetani et al, 2004;Carneiro and El-Deiry, 2020;Yu et al, 2019). On the other hand, the increase in the interrelated expressions of card4 and apaf-1 in the apoptotic pathway with the administration of aqueous extract may indicate that the aqueous extract causes apoptosis, but the pathway may be different.…”
Section: Sezersupporting
confidence: 49%
“…We determined by qRT-PCR that S. cuneifolia extracts showed apoptosis-triggering effects on pro-apoptotic and anti-apoptotic gene expressions in DLD1 cells. In the present study, apaf-1, tp53, card4 and Casp-3 genes were found to be upregulated in cancer cells after exposure to these extracts; these proteins play an important role in tumour suppression, cell cycle arrest and application phase of cell apoptosis (Delbridge et al, 2012;Kao et al, 2015;Kobayashi et al, 2000;Mattson and Bazan, 2012;Umetani et al, 2004;Carneiro and El-Deiry, 2020;Yu et al, 2019). On the other hand, the increase in the interrelated expressions of card4 and apaf-1 in the apoptotic pathway with the administration of aqueous extract may indicate that the aqueous extract causes apoptosis, but the pathway may be different.…”
Section: Sezersupporting
confidence: 49%
“…ENO2 can function as on oncogene, either in neuronal malignancies or in other cancer types, such as lung, breast, and prostate cancer [126][127][128]. Recent evidence was provided that the C-term domain of ENO2, which is not necessary for metabolic activity, activates the MAPK/ERK signaling pathway and thus promotes proliferation and migration of BRAV V600E-mutated CRC cells [129]. In this regard, in our study, we demonstrate that the combined knockdown of ALDOC and ENO2 significantly reduced lactate production and consequently attenuated the sphere-forming ability of both LUAD and breast cancer cell lines both in nutrient-rich and nutrient-restricted conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the integration of transcriptomic and proteomic data highlighted that NOL3 was up regulated in all 3D vs 2D conditions both at gene and protein levels. NOL3 functions as a suppressor of both intrinsic and extrinsic apoptosis through several mechanisms, including the blockage of death-inducing signaling complex (DISC) assembly, the limitation of caspase-8 for DISC-mediated activation, and the inactivation of pro-apoptotic BAX [100].…”
Section: Discussionmentioning
confidence: 99%